The Implementation of Online Classes in Mediating Reading Activities in the Blended Learning Model - Senny Suzanna Alwasilah (Soegijapranata Catholic University, 2020)
As technology develops, the quality of language learning is able to improve due to the ease and innovation in accessing information and media as a learning tool, so that it can provide enormous benefits, especially in writing learning activities. Therefore, this study aims at examining the extent to which digital storytelling utilizes Storybird (a web tool for writing story) to mediate students’ learning activities. This study employed qualitative netnography as a research method. Through netnography, there are three beneficial aspects of students’ creative writing learning, which are: 1) Storybird is a platform for collaborative writing activities, 2) digital storytelling can develop students’ higher order thinking skills, and 3) digital storytelling becomes a method for implementing creative and innovative language learning. This study contributed to provide the understanding of how digital storytelling can be a learning method that provides broader thinking space for students. In addition, the purpose of this study is to invite students to participate in the process of learning creative writing.Seiring perkembangan teknologi, kualitas pembelajaran bahasa mampu meningkat disebabkan oleh kemudahan dan inovasi dalam mengakses informasi dan media sebagai sarana pembelajaran, sehingga hal tersebut dapat memberikan manfaat yang sangat besar, terutama dalam aktivitas pembelajaran menulis. Oleh karena itu, penelitian ini ditujukan untuk mengkaji sejauh mana digital storytelling dengan memanfaatkan Storybird (sebuah webtool untuk menulis cerita) dalam memediasi aktifitas belajar siswa. Penelitian ini menggunakan metode netnography kualitatif sebagai model penelitian, Melalui netnography, penelitian ini mendapatkan temuan bahwa terdapat tiga aspek manfaat terhadap pembelajaran menulis kreatif siswa, yaitu: 1) Storybird menjadi platform dalam melakukan kegiatan menulis kolaboratif, 2) digital storytelling dapat membantu mengembangkan kemampuan higher order thinking siswa, dan 3) digital storytelling menjadi metode untuk menerapkan pembelajaran bahasa yang kreatif dan inovatif. Kontribusi dari penelitian ini untuk memberikan pemahaman bagaimana digital storytelling dapat menjadi metode belajar yang dapat memberikan ruang berfikir yang lebih kepada siswa. Adapun tujuan dari metode ini adalah untuk mengajak siswa agar lebih terlibat ke dalam proses pembelajaran menulis kreatif.